A SUCCINCT VIEW ON ART MUSIC IN THE UNITED STATES OF AMERICA DURING THE 1980s - FERARU, Tudor (Studia Universitatis Babes-Bolyai Musica, 2012)
The article looks at the state of art music and concert life in America, between 1980 and 1990. It proposes a concise description of the various currents and tendencies that were manifesting within the “serious music” establishment. A few of the most important directions in music composition are presented and placed in the broader context of the late 20th-century musical phenomenon. The study also provides insight into the work of some of the most prominent American composers who were active during this period. Both technical and aesthetic aspects of their creative output are described. Finally, the paper includes a selective list of musical works, representative of the several discussed currents and authors.